Jean Vigo - Temple, Michael, 1963-; Manchester University Press (Manchester, UK : Manchester University Press, 2019)
'Jean Vigo is one of the legendary figures of world cinema, whose films 'L'Atalante' and 'Zéro de conduite' still inspire young audiences today. Film historian Michael Temple explores Vigo's intense career and asks why it has had such a long-lasting impact on film culture, not just in France, but also for generations of filmmakers, critics, and moviegoers around the world. Each film is examined under four headings:- social and political context- the making of the film, from conception to release-detailed analysis of narrative structure, main stylistic features and dominant themes- the reception of the film and its critical reputationAccessibly written, this will be essential reading for students, teachers, film enthusiasts and researchers, indeed for anyone who is interested in the cinema as a living art form' --Back cover.
List of plates -- Series editor's foreword -- Acknowledgements -- 1. The cinema incarnate -- 2. On the subject of documentary -- 3. The personal and the political -- 4. An unknown masterpiece -- 5. Visions of Vigo -- Filmography -- Select bibliography -- Index.
Made available via: manchesterhive.
Includes bibliographical references and index.
In English.
Print version record
JSTOR
Keywords: Vigo, Jean, -- 1905-1934 -- Criticism and interpretation; Vigo, Jean, -- 1905-1934; Motion picture producers and directors; Producteurs et réalisateurs de cinéma.; filmmakers; Film, TV and radio; Individual film directors, film-makers.; PERFORMING ARTS -- Film -- History & Criticism; PERFORMING ARTS / Film / History & Criticism; Motion picture producers and directors; The Arts -- Performing arts -- Films, cinema -- Film history, theory & criticism; Electronic books; Criticism, interpretation, etc